Age-Based Analysis of Self-Harm Behaviors Among Instagram Users - Erwinda, Lira; Kurnaedi, Nedi (Bulletin of Counseling and Psychotherapy, 2024)
The suicide rate among adolescents and young adults has risen to the position of the second greatest cause of mortality. Research on the influence of social media on the suicide risk or reduction of risk among young people is a relatively new and rapidly increasing field of study that requires the attention of a wide variety of specialists working in the field of mental health services. This research aims to describe the condition of self-harm based on the age of individuals who use the Instagram platform. This research is comparative research obtained through purposive random sampling. The sample for this research was 288 respondents consisting of various ages. Data were collected using a self-harm instrument with 18 items in a four-point response format. The analysis technique uses an item response theory (IRT) approach with Rasch Model analysis. This research tested descriptive and differences using Anova with the help of WINSTEPS Version 5.0.0. The results show that there is a significant difference between self-harm among Instagram users based on age. In addition, Instagram users aged 18–20 in late teenage development fill out the self-harm instrument more than other age groups. Instagram users had low self-harm rates, according to the study. This study recommends that policymakers and scholars should monitor social media mental health trends.